Preparation of Multifunctional Dopamine-Coated Zerovalent Iron/Reduced Graphene Oxide for Targeted Phototheragnosis in Breast Cancer - Chia-Hua Lin; Yi-Chun Chen; Pin-I. Huang (Nanomaterials, 2020)
The present study aimed to develop a multifunctional nanoparticle platform with properties that are beneficial in imaging, targeting, and synergistic cancer phototherapy. To this end, we synthesized novel nanoparticles composed of polydopamine, nano zero-valent iron (nZVI), and reduced graphene oxide (rGO). We immobilized nZVI on the surface of GO (nZVI/GO), then further modified nZVI/GO with dopamine to form polydopamine-conjugated nZVI/rGO (nZVI/rGO@pDA). Because nZVI/rGO@pDA absorbs near infrared radiation (NIR) and binds biomolecules of cancer cells, this platform is highly efficacious in photothermal and photodynamic cancer therapy and enables specific targeting of breast cancer cells. Use of nZVI/rGO@pDA at a low concentration (10 μg/mL) resulted in irreversible damage to MCF-7 cells under NIR irradiation (808 nm) without inducing cytotoxic effects in normal cells. Furthermore, nZVI/rGO@pDA showed high sensitivity in magnetic resonance imaging (MRI), comparable to nZVI@pDA, even at low concentration. Monitoring the treatment response through evaluation of MRI signal intensity of nZVI/rGO@pDA in phototherapeutic therapy revealed that the novel material combines the advantages of nZVI, rGO, and pDA to provide specific targeting capabilities, excellent biocompatibility, and cancer phototherapeutic and tumor imaging abilities. Thus, this platform offers great potential in terms of imaging and therapeutic effects in phototherapy treatment for breast cancer.